IMPROVING THE STUDENTS’ READING COMPREHENSION THROUGH KNOW-WANT-LEARN STRATEGY - Ariana Ariana; Rahmawati Umar (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2013)
Improving The Students’ Reading Comprehension Through Know-Want-Learn Strategy at the first-grade students of SMA Negeri 18 Makassar. The objective of this research was intended to explain the improvement of the students’ interpretative and literal reading comprehension through Know-Want-Learn Strategy at the first-grade students of SMA Negeri 18 Makassar especially in class X 3. The strategy of this research was a Classroom Action Research (CAR) consisted of two cycles, one cycle consisted of four meetings. It means that there were eight meetings for two cycles. This classroom action research was done at the first-grade students of SMA Negeri 18 Makassar in Daya Regency for English subject. As the subject in this research was class X 3 in the 2012-2013 academic year with students’ number of about 32 students. Those consist of  22 women and 10 men. The instrument of this research was observation sheet and reading test or evaluation. The findings of the research were students achievement in reading comprehension was 54,07 in D-test, then Cycle I is 69,07 and it becomes 73,81 in Cycle II. The students'  activeness in learning reading comprehension in the first meeting of Cycle I was 45,39% then it becomes 90,78% in the fourth meeting of Cycle II.Keyword: Improving, reading, know, want, learn, strategy.